PENYALAHGUNAAN HAK DAN WEWENANG ORGANISASI MASYARAKAT DI KELURAHAN KEDAUNG, TANGERANG SELATAN, BANTEN - Dwi Putranto Priyono; Wati Nilamsari (Jurnal Ilmiah Dinamika Sosial, 2021)
Community Organizations were originally formed to accommodate the aspirations of every community in every region in Indonesia. Community Organizations or so-called Ormas, is one of the main forums in the independence process. Community Organization is a collection of individuals who form a group that is acquired by the state, both formal and informal. But on the one hand, along with its development, the function of CSOs as a forum for movement for the community has shifted its function into a form of movement that tends to be negative. This study aims to find out some of the social problems caused by the abuse of the rights of civil society organizations in the Kedaung village. The background of the problem that has been formulated into several questions, including what is the background of clashes between Community Organizations can occur, what policies have been set by the government to address this problem and what are the effects on residents who are not involved with conflicts between CSOs This observation refers to the analysis of the paradigm of resource mobilization to answer the formulation of problems related to conflicts between CSOs that occur in the Kedaung village so that the struggle for resources in the form of land can cause social problems that disturb residents around Kedaung. Research in this journal applies qualitative methods in the form of interviews, observations and several literature studies. This study assesses that the existing CSOs in the Kedaung sub-district fight over resources in the form of land. The so-called land is a parking lot in several minimarkets where they make extortion to minimarket visitors.